Alat Berupa Scanner Reading Audio Untuk Para Penyandang Tunanetra Yang Berfungsi Untuk Membaca Isi Buku Tanpa Menggunakan Huruf Braille Guna Meningkatkan Mutu Sumber Daya Manusia Indonesia - Pracia Maheswari, Nandana; Naufal Ramadhan, Daffa; Mutiara Rengganis, Anandayu; Hisya Arivantoro, Syahnakitry; Oktavina Radianto, Denny (Rifa'Institute, 2023)
The five senses are a source of information, one of which is the sense of sight. Therefore, it can be assumed that if a person's sense of sight is impaired, then his abilities and activities will be very limited because the information obtained will be very much reduced when compared to people who have normal vision. People who experience disturbances in their sense of sight are generally called blind. In general, people with visual impairments read through braille using their sense of touch, but not all books can be made in braille. There are many books that have hundreds of pages, it is impossible to make the book in the Braille version, of course, it will be more difficult and time consuming and expensive. Based on pre-research on the vice principal of SLB YPAB Surabaya, children with visual impairments listen more and draw information from situations to memorize and apply it in everyday life. Furthermore, children rarely get insight from reading materials, especially books that are currently up to date. That's why we developed SDB(Scanning Digital Book). This tool has several popular book titles that you can choose according to genre and are more up to date. Our goal in conducting this research is to find out how much the blind people are satisfied with the tools we make and can be useful in increasing the literacy and human resources of blind children in the coming years